Big Data and the Emerging Role of Libraries (2019)
Technological advancement has led to a massive increase in the amount of data being generated and accumulated daily. As a result, libraries no longer manage only print collections. They are also involved in managing materials that are bom digital from an ever- growing range of sources using new technologies. This has led to the emergence of big data and new services in libraries. As the library’s tradition changes, so also the research landscape changes. How is the library responding to this contemporary challenge for research? This chapter presents an overview of big data projects involving libraries. Some publications on big data projects were retrieved from databases such as LISTA and Google. Relevant websites and blog post were also consulted. The discussion focused on the emergence of big data and the library’s emerging role in the research landscape. The review reveals the libraries’ engagement with big data and challenges encountered, and recommends ways of addressing these challenges.